2016
DOI: 10.1177/0961203316629558
|View full text |Cite
|
Sign up to set email alerts
|

Postural Orthostatic Tachycardia Syndrome (POTS) – A novel member of the autoimmune family

Abstract: Postural orthostatic tachycardia syndrome (POTS) is a heterogeneous disorder of the autonomic nervous system in which a change from the supine position to an upright position causes an abnormally large increase in heart rate or tachycardia (30 bpm within 10 min of standing or head-up tilt). This response is accompanied by a decrease in blood flow to the brain and hence a spectrum of symptoms associated with cerebral hypoperfusion. Many of these POTS-related symptoms are also observed in chronic anxiety and pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 40 publications
(66 reference statements)
0
36
1
2
Order By: Relevance
“…Autoimmunity has been implicated in the pathogenesis of POTS . We found no major differences in autoantibody testing.…”
Section: Discussioncontrasting
confidence: 42%
“…Autoimmunity has been implicated in the pathogenesis of POTS . We found no major differences in autoantibody testing.…”
Section: Discussioncontrasting
confidence: 42%
“…A recent study showed that serum levels of autoantibodies to several autonomic receptors were higher in ME/CFS patients than in healthy controls (41). Similar autoantibodies were detected in postural orthostatic tachycardia syndrome (42) and in complex regional pain syndrome (43), conditions with some resemblances to ME/CFS, affecting fertile women after a triggering event (44,45). Likewise, autoantibodies in ME/CFS may interfere with key metabolic signaling pathways involving factors such as HIF1 (24) and PPARs, as well as AMPK, which was abnormally activated in skeletal muscle cells of ME/CFS patients (46).…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, Blitshteyn recently determined the high prevalence of positive ANA and other autoantibodies and the high prevalence of comorbid autoimmune disorders that exist in patients with POTS 8, 9. Sandroni and Low demonstrated occasional positivity to gAChR antibodies in POTS patients 10.…”
Section: Introductionmentioning
confidence: 99%